Nitellopsis obtusa (Desv.) J. Groves : A new charophytic record for Bangladesh - Naz, Sabrina; Diba, Nasrin Jahan; Zaman, M. (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. Keywords: Nitellopsis obtusa; Characeae; New record; Bangladesh. DOI: 10.3329/bjpt.v17i2.6701 Bangladesh J. Plant Taxon. 17(2): 203-207, 2010 (December)